The 15th Symposium on New Trends in Audio and Video Technology - New Trends in Audio; Video, 15th International Symposium (Archives of Acoustics, 2015)
In 2014 the XV Symposium New Trends in Audio and Video organized by the Polish Section of Audio Engineering Society under the honor patronage of the National Broadcasting Councils (KRRiT) and Acoustical Committee of Polish Academy of Science was held in Wroclaw in September. The main topics of the conference covered mostly all domains of audio and video engineering, i.e. the sound visualization, measurement technique, perception and quality assessment, data reduction in audio and video signals, sound reinforcement, mixing and mastering technology, and many others. The extra attention has been paid for the problems of loudness of audio programs in radio and TV broadcasting. Over 50 people from different branches of audio and video technology from Poland as well as from abroad participated this Symposium and shared their knowledge and experiences during the paper sessions, technical tours, workshops and special presentations performed by Dolby Poland on the field of Object Audio in wide spectrum. Below there is a selection of abstracts of the papers presented at this event.